Avaliação de uma análise automatizada para determinação de atividade enzimática - Estrela, Mariely Cordeiro (2017)
The Molecular Biology Institute of Paraná (IBMP) acts in the production of inputs for detection of diseases. In partnership with Bio-Manguinhos (Fiocruz), it is currently responsible for manufacturing the amplification module of the Brazilian NAT KIT for HIV (AIDS), HCV (Hepatitis C) and HBV (Hepatitis B), besides other products for molecular diagnostics. The molecular test basically consists of amplifying the genetic material of the virus (DNA or RNA) through the real-time PCR (polymerase chain reaction) technique, which enables detection of the pathogen from small amounts of nucleic acid present in the sample. The PCR reaction occurs by the activity of Taq DNA Polymerase, a thermostable enzyme widely used for selective replication of DNA fragments. This enzyme was isolated from a thermophilic bacterium, called Thermus aquaticus and is produced by the IBMP, being considered an input of high criticality. One of the steps in controlling the production process of this enzyme is the evaluation of the enzymatic extract and the determination of the activity of the purified enzyme. The quantification method consists in evaluating the enzymatic activity through the conventional PCR methodology, followed by an analysis of the electrophoretic profile of the agarose gel samples. However, the methodology currently used presents a great subjectivity, since the interpretation of results can suffer variations when analyzed by different operators. The objective of the present work is to evaluate the implementation of an automated analysis of the results through digital image processing, which in addition to facilitating the laboratory routines, can be the key to results with a greater degree of precision and repeatability, thus eliminating the subjective bias of the analyst. The new methodology of analysis implies less interference of the analyst in the interpretation of the results. The proposed method was tested in a set of images and the obtained results were compared with the values of the manual analysis currently used. The results were considered promising because the automated analysis, besides significantly reducing the analysis time, allows a standardization of the results.